2023
DOI: 10.1038/s41598-023-28870-z
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of an electrically charged hydrogel implanted into a traumatic brain injury model for stepwise neuronal tissue reconstruction

Abstract: Neural regeneration is extremely difficult to achieve. In traumatic brain injuries, the loss of brain parenchyma volume hinders neural regeneration. In this study, neuronal tissue engineering was performed by using electrically charged hydrogels composed of cationic and anionic monomers in a 1:1 ratio (C1A1 hydrogel), which served as an effective scaffold for the attachment of neural stem cells (NSCs). In the 3D environment of porous C1A1 hydrogels engineered by the cryogelation technique, NSCs differentiated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Therefore, the CCI-SA-sTBI model mimics resection of contused tissue to leave behind a tissue cavity, and the intracavitary delivery of 3D constructs represents a novel paradigm for assessing lesion volume deficits, cellular repair, biomaterial integration and cross-talk with native brain tissue. The (CS-A)CP hydrogel implanted animals demonstrated significantly accelerated recovery of forelimb motor function, 5-weeks after sTBI, which was likely mediated by the intralesional presence of neuroprotective and neuritogenic scaffolding [20,21,64,65]. Immunohistochemical analyses of perilesional tissue confirmed that the hydrogel implant was able to prevent neuronal as well as axonal loss and demonstrated greater synaptic vesicle presence, indicating tissue recovery.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, the CCI-SA-sTBI model mimics resection of contused tissue to leave behind a tissue cavity, and the intracavitary delivery of 3D constructs represents a novel paradigm for assessing lesion volume deficits, cellular repair, biomaterial integration and cross-talk with native brain tissue. The (CS-A)CP hydrogel implanted animals demonstrated significantly accelerated recovery of forelimb motor function, 5-weeks after sTBI, which was likely mediated by the intralesional presence of neuroprotective and neuritogenic scaffolding [20,21,64,65]. Immunohistochemical analyses of perilesional tissue confirmed that the hydrogel implant was able to prevent neuronal as well as axonal loss and demonstrated greater synaptic vesicle presence, indicating tissue recovery.…”
Section: Discussionmentioning
confidence: 86%
“…During ischemic damage, the brain’s blood supply is reduced, leading to the loss of neuroglial cells, tissue framework, and extracellular matrix [ 69 ].…”
Section: The Nervous Systemmentioning
confidence: 99%
“…The effects of HA/Gel/SAB/VEGF hydrogel in repair of brain injury was evaluated by a traumatic brain injury model with cavity formation in mice [46]. After 14 and 28 days of hydrogel injection into the brain defects, macroscopic observations of the brain defects were firstly performed, and the images are shown in Figure 7A.…”
Section: Ha/gel/sab/vegf Hydrogel Promotes the Repair Of Brain Injury...mentioning
confidence: 99%
“…A TBI model was established by using 7-to 8-week-old C57BL/6 mice [46]. After anesthesia with isoflurane, the mice were immobilized on a brain stereotaxic device.…”
Section: Establishment Of Tbi Model and Hydrogel Implantationmentioning
confidence: 99%